2021
DOI: 10.31616/asj.2020.0086
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes in Spinal Tuberculosis: A Review of the Literature

Abstract: Spinal tuberculosis often leads to neurological deficit and subsequent deterioration in functional outcomes. This review assesses the recent evidence on functional outcomes in spinal tuberculosis, highlighting functional recovery, assessment tools for functional measures, and associative factors for functional recovery. Using PubMed, a literature search was done using the terms "spinal tuberculosis," "tuberculous spondylitis," "tuberculous spondylodiscitis," and "functional outcome" for original articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Bhojraj et al [18] reported more than 98% spinal tuberculosis patients can be cured by simple chemotherapy and avoided surgery. No signi cant difference in functional outcome was found between conservative management and surgery for cases with uncomplicated spinal tuberculosis [19].…”
Section: Discussionmentioning
confidence: 83%
“…Bhojraj et al [18] reported more than 98% spinal tuberculosis patients can be cured by simple chemotherapy and avoided surgery. No signi cant difference in functional outcome was found between conservative management and surgery for cases with uncomplicated spinal tuberculosis [19].…”
Section: Discussionmentioning
confidence: 83%
“…But the most complicated form is central nervous system disease, which has severe consequences for the patient if not diagnosed or treated late. Sometimes, due to the ambiguity and unknown clinical symptoms, the diagnosis is made late or even, in some cases, is made incorrect (2). Therefore, clinical awareness about this disease should always be considered to reduce patients suffering from the dangerous consequences (3).…”
Section: Introductionmentioning
confidence: 99%
“…Its involvement occurs in various forms, such as spinal cord tuberculosis, arachnoiditis, radiculomyelitis, and syringomyelia without vertebral involvement. These complications, which can be a complication of meningitis, are rare and dangerous and can only lead to complete recovery if diagnosed and treated early (2). Tuberculosis can damage enzymes, DNA, and other macromolecules and induce oxidative stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…The number of reported cases has been rising ever since and its incidence is highest in developing countries. It accounts for about 2 -15%% of cases of TB, representing the most common target of osteoarticular TB (Snider et al, 2017;Yong et al, 2020). In Malaysia, there have been 25,713 cases recorded for tuberculosis in 2018 alone with an estimated incidence rate of 92 per 100000 cases.…”
Section: Introductionmentioning
confidence: 99%
“…To identify factors that might predict a poor functional outcome recovery in spinal tuberculosis patients. These patients may require more aggressive rehabilitation to give them a better chance at achieving their best functional outcome recovery (Yong, 2020).…”
Section: Introductionmentioning
confidence: 99%